Kepemimpinan Camat Dalam Meningkatkan Kinerja Pegawai (Studi pada Kecamatan Wates Kabupaten Kediri) - Andita, Nike Viky (Jurnal Administrasi Publik, 2016)
Abstract: Head Leadership in Improving Employee Performance. Results of this research indicate that the district head as the leader of a local government in the district of Kediri Regency Wates, it has an important role in supporting, realize and develop in order to become better governance. In this case the leader of a more targeted use of situational theory and the type of leadership that is democratic, it is evident during the process of decision making, delegation of authority, supervision and communication always work in coordination with the employees. Employee performance appraisal in the districts leads on quality, quantity and timeliness of employees in completing its tasks by using situasioal leadership style, because in the assessment process, the leader prefers responsibility as a form of trust to its employees. In addition the District Wates, Head as the leader of the agency is required to always provide motivation to overcome problems both from within and from outside which may cause adverse effects on the performance of employees. Keywords: Leadership, employee performance Â  Abstrak: Kepemimpinan Camat Dalam Meningkatkan Kinerja Pegawai. Hasil dari penilitian ini menunjukkan bahwa camat sebagai pemimpin suatu pemerintahan daerah di Kecamatan Wates Kabupaten Kediri, sangat mempunyai peran penting dalam mendukung, mewujudkan dan mengembangkan pemerintahan supaya menjadi lebih baik. Dalam hal ini pemimpin lebih terarah menggunakan teori situasional dan tipe kepemimpinan yang demokratis, hal ini terlihat jelas pada saat proses pengambilan keputusan, pendelegasian wewenang, pengawasan kerja dan komunikasi yang selalu berkoordinasi dengan pegawainya. Penilaian kinerja pada pegawai kecamatan tersebut mengarah pada kualitas, kuantitas dan ketepatan waktu pegawai dalam menyelesaikan tugasnya dengan menggunakan gaya kepemimpinan situasioal, karena dalam proses penilaian, pemimpin lebih mengutamakan tanggung jawab sebagai wujud kepercayaan kepada pegawainya. Selain itu Kecamatan Wates, Camat sebagai pemimpin instansi dituntut untuk selalu memberikan motivasi guna mengatasi masalah baik dari dalam maupun dari luar yang dapat menimbulkan akibat buruk pada kinerja pegawai. Â  Kata kunci : kepemimpinan, kinerja pegawai